Flipped Classroom Integrated with Ethnoscience: Innovative Learning Tools in Science Learning - Putri, Helmalia; Jufrida; Dani, Rahma (Indonesian Journal of Educational Research and Review, 2023)
Learning tools for a teacher are an obligation that must be owned, because they become a guide for a teacher in carrying out the teaching and learning process. Learning devices are the initial stage in the learning process, so the quality of the devices used must make students more active in the learning process. The aim of this study is to develop learning devices of flipped classroom independent curriculum integrated with ethnoscience materials applying the principles and concepts of heat. This study uses a 4D model, but researchers conduct research only at the develop stage. The subjects of this study were 2 Physics lecturers and teachers. The data collection method used in this research is in the form of interviews and expert validation sheets, namely pedagogy, materials and media. Data analysis techniques in this study consisted of qualitative data, quantitative data and validation questionnaire data. The result produce flipped classroom learning device integrated with ethnoscience in the material applying the principles and concepts of high school physics heat. Based on the validation data of lecturers as experts and teachers as users, it can be concluded that the validation learning device products get results in all aspects in very good categories.